Analytic model for MPEG-4 and H.263 encoded video traces - Adiche, H. (2003)
Summary form only given. We present the analysis of statistical distributions of 1-hour long publicly available empirical samples of MPEG-4 and H.263 encoded video traces. Each video has been encoded to different quality levels. The results of our analysis show that: i) although the autocorrelation of the studied traces asserts long-range dependence, however, the distribution of the same traces is not heavy-tailed; ii) for different quality levels, the traces belong to the same statistical distribution; iii) most of the studied traces show long-tail behavior which can be modeled using lognormal distribution function.